Feeding habits of Tinfoil barb, Barbonymus schwenenfeldii in the Tasik River, South Labuhanbatu, North Sumatra, Indonesia - Desrita Desrita; FANNI K. HASUGIAN; ERI YUSNI; VINDY R. MANURUNG; RIDAHATI RAMBEY (Society for Indonesian Biodiversity, 2021)
Abstract. Desrita, Hasugian FK, Yusni E, Manurung VR, Rambey R. 2021. Feeding habits of Tinfoil barb Barbonymus schwenenfeldii in the Tasik River, South Labuhanbatu, North Sumatra, Indonesia. Biodiversitas 22: 2131-2135. Research on feeding habits of Tinfoil barb, Barbonymus schwanenfeldii was carried out in the Tasik River from July to August 2020. This study aims to determine the composition of foods consumed by Tinfoil barb fish, and the availability of natural food in the Tasik River from 3 sampling stations. Fishes were caught using a gillnet with a mesh size of 3.18 cm, then the fish samples were dissected, and the digestive tract was taken and preserved with 10% formalin. A total of 138 Tinfoil bars were caught for this study. Analysis of stomach contents found that Tinfoil barb ate phytoplankton (41-48%) as the primary food, moss (25-38%), plant pieces (13-17%), worms (2-11%) as a complementary food and few of insects (0-4%), zooplankton (0-1%) as other foods. Based on analysis of food item values, all types of food and ratio within the intestine length and the total length showed that Tinfoil Barb was classified as omnivorous. The availability of natural foods for Tinfoil Barb in the Tasik River consists of the genera Asteroinella, Bacillaria, Bidulphia, Cestom, Gyrosigma, Gonatozygon, Oscillatoria, and  Thalassiora.